Oral hygiene status of depressed patients - Permatasari, Putri; Yubiliana, Gilang; Iskandarsyah, Aulia (Universitas Padjadjaran, 2020)
Introduction: Oral hygiene is one of the most critical factor in maintaining oral health. Depression symptoms may affect an individual’s oral health due to poor health behaviour, making depressed individuals prone to oral diseases such as caries and periodontal diseases. This study was aimed to obtain the oral hygiene status overview of depressed patients in West Java Psychiatric Hospital. Methods: This study was an observational descriptive with a cross-sectional approach to depressed patients (F.32 ICD Code). The measuring instrument used was Oral Hygiene Index-Simplified (OHI-S). Based on OHI-S, oral hygiene can be assessed into poor within 3.0 – 6.0 score point, fair within 1.3-3.0 score point, or good within 0.0 – 1.2 score point. Results: There were 30 respondents recruited using a purposive sampling method. Based on the plaque index, 1 respondent (3%) fell into good category, 23 respondents (77%) fell into the fair category, and 6 respondents (20%) fell into poor category. Based on the calculus index, 7 respondents (23%) fell into good category, 10 respondents (60%) fell into the fair category, and 5 respondents (17%) fell into poor category. Based on OHI-S, 2 respondents (7%) fell into the good category, 18 respondents (60%) fell into the fair category, and 10 respondents (33%) fell into poor category. Conclusion: Oral hygiene in-dex of depressed patients was categorised as fair.